2013
DOI: 10.1590/s1516-89132013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Demography and structures population of Actinostemon concolor (Spreng.) Müll. Arg. (Euphorbiaceae) in flooded areas in Southern Brazil

Abstract: The aim of this work was to analyze the size and spatial structures and demography of Actinostemon concolor (Spreng.) Müll. Arg. (Euphorbiaceae) in the flooded areas of Mata dos Godoy State Park. Fifty plots of 100 m 2 were established and three surveys were conducted. All the individuals were measured, mapped and divided into categories as seedlings, juveniles and adults. The coefficient of skewness, L-function of Ripley, and the matrix population models were used in the study. The population showed positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…The woody understory Actinostemon concolor was registered once in the regeneration layer (Table ). This species was classified as nontolerant to flooding and with high mortality in areas with high cover of herbs and litter (Bianchini et al, 2013). Population of Maytenus dasyclados , also recorded once in the regeneration layer, other studies showed that the species is decreasing in Southern Brazil as a result of anthropogenic fragmentation (Reichmann et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The woody understory Actinostemon concolor was registered once in the regeneration layer (Table ). This species was classified as nontolerant to flooding and with high mortality in areas with high cover of herbs and litter (Bianchini et al, 2013). Population of Maytenus dasyclados , also recorded once in the regeneration layer, other studies showed that the species is decreasing in Southern Brazil as a result of anthropogenic fragmentation (Reichmann et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A relação positiva da densidade de indivíduos com os terços superiores em ambas as pedoformas pode ser uma resposta direta ao efeito do relevo, visto que as cotas mais elevadas, próximas ao topo, apresentam menor declividade e terreno mais plano (Tabela 5), impondo menos restrições ao estabelecimento das plantas, especialmente aquelas ocasionadas por ação da gravidade. & Monteiro, 2002;Lorenzi, 2009a;Bianchini et al, 2013). Portanto, sua associação forte à pedoforma côncava (as 2 últimas foram encontradas exclusivamente nela) pode ser reflexo da maior disponibilidade de água proporcionada pela curvatura do terreno.…”
Section: Fonte: Os Autores (2013)unclassified